Bringing human information behaviour into information systems research: an application of systems modelling (Information Research: An International Electronic Journal)
In their influential paper, Dervin and Nilan compared and contrasted the "traditional" and "alternative" paradigms for human information behaviour research, highlighting the inadequacies of the former and promoting the importance of the latter. In this paper, we argue that the two paradigms are not irreconcilable. We offer a research framework that allows qualitative and quantitative views of the same problem to be combined using systems models. We demonstrate how this approach can be used to reconcile the six key differences between the two paradigms as argued by Dervin and Nilan.